2018
DOI: 10.1016/j.ijid.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Emergent lineages of mumps virus suggest the need for a polyvalent vaccine

Abstract: Mumps outbreaks among vaccinated patients have become increasingly common in recent years. While there are multiple conditions driving this re-emergence, convention has suggested that these outbreaks are associated with waning immunity rather than vaccine escape. Molecular evidence from both the ongoing American and Dutch outbreaks in conjunction with recent structural biology studies challenge this convention, and suggest that emergent lineages of mumps virus exhibit key differences in antigenic epitopes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 31 publications
1
34
0
1
Order By: Relevance
“…It has been found that the efficacy of the mumps vaccine containing the Jeryl Lynn strain was 95-96% [90]. The effectiveness of two doses of MMR immunization is not as high as expected, and outbreaks have been reported in countries with high vaccine coverage [91][92][93]. It was reported that the estimated vaccine effectiveness for one-dose MMR vaccination was 85.4% (95% CI: 67.3-93.4%), and that for two-dose MMR vaccination was 88.5% (95% CI: 78.1-93.9%) in a study in Spain [94].…”
Section: Jeryl Lynn Strain Mumps Vaccinementioning
confidence: 99%
“…It has been found that the efficacy of the mumps vaccine containing the Jeryl Lynn strain was 95-96% [90]. The effectiveness of two doses of MMR immunization is not as high as expected, and outbreaks have been reported in countries with high vaccine coverage [91][92][93]. It was reported that the estimated vaccine effectiveness for one-dose MMR vaccination was 85.4% (95% CI: 67.3-93.4%), and that for two-dose MMR vaccination was 88.5% (95% CI: 78.1-93.9%) in a study in Spain [94].…”
Section: Jeryl Lynn Strain Mumps Vaccinementioning
confidence: 99%
“…lack of a durable T-cell mediated response, as well as antigenic differences between vaccine and circulating mumps strains, (1,4,(7)(8)(9)(10)(21)(22)(23)(24). As such, the mismatch between vaccine and circulating mumps stains has also prompted the consideration of a polyvalent vaccine (1,25) In our study, most of the samples submitted for MuV testing were CSF and blood specimens. However, information on the clinical presentation of the patients from whom specimens were collected was not Our finding of a male predominance with regards to infections is similar to what has been reported in other studies (26,27).…”
Section: Operational Definitionsmentioning
confidence: 97%
“…Besides these more obvious antigenic changes, resulting in serotype replacements, less-well defined and more diffuse antigenic changes may also change the effectiveness of particular vaccines. This is illustrated by the reemergence of mumps in highly vaccinated populations, indicating waning of the vaccine-acquired immune response and reduced capability to protect against antigenically divergent strains [128,129].…”
Section: Evolution Of the Pathogensmentioning
confidence: 99%